KARAKTERISASI TAKSONOMI DAN POTENSI ISOLAT FUNGI LOKAL SEBAGAI BAHAN BAKU NUTRASITIKAL - Ivan
Indonesia is a country which hold enormous biodiversity and fungi is one of them. The biodiversity itself is potential for Indonesia to thrive in food and medicinal industries. However, further exploration is needed to know whether it has a good potential in nutraceuticals. In this study, a local fungal isolate which was found in GunungGeulis, West Java is characterized and analyzed. Taxonomy characterization was carried out using ITS DNA sequence analysis and NSI1 as primer. Measurements of lovastatin, chitin and beta-glucan was carried out to analyze its nutraceutic potentials. Lovastatin content was measured using high performance liquid chromatography (HPLC) technique. Chitin content was measured using colorimetry method. Beta-glucan content was measured using gravimetry method. The result showed that the isolate has 100% similarity with Coriolopsis strumosa KUC20110916-07 which was reported by Jang, et al. in 2014. The result also showed that the isolate has chitin, lovastatin, and beta-glucan content respectively 22,62 ± 2,86% (g/g), 1,91 ± 0,2 ppm, 20,65 ± 2,47 % (g/g). The isolate’s lovastatin content is relatively inferior compared to other fungi which has lovastatin content ranging over 1-55 ppm. The chitin content is also lower than M. rouxii(44,5% g/g) which is a common chitin producer in industries. The beta-glucan content is also lower than common edible mushroom like L. edodes(43,7% g/g). These amounts can be further enhanced by further medium optimization and genetic engineering.